Nível de aderência das sociedades por ações às normas IFRS no reconhecimento de debêntures conversíveis emitidas em ofertas públicas no período 2009 a 2017 - Soares, Osvaldo Alves (2018)
The capital market has developed a variety of instruments to supply companies with financial resources; however, it has been proved difficult to distinguish them as equity or liability instruments. Known as financial instruments, they are contracts that generate financial asset to a company and financial liability or equity to another. Among such instruments are the so-called compound instruments, such as the convertible bonds, which combine an equity component to a liability component. The present study aims at answering the following research question: what is the degree of adherence of Brazilian public companies to the IFRS rules in their recognition of convertible bonds issued in the period between 2009 and 2017? To answer this question the work is divided into three chapters dedicated to presenting, respectively, the theoretical framework of the study, the methodological procedures followed, and the analysis and interpretation of the data collected. The work follows a qualitative approach, and is both exploratory and descriptive in nature. Methodological procedures include three main stages: analysis of initial recognition of convertible bonds; elaboration of a checklist of the recognition forms used; and the evaluation of the companies’s degree of adherence to the IFRS norms. Six convertible bond issues were identified, and the companies differed in their way of recognizing the bonds. Only one of the issuers correctly identified the financial instrument issued, and none of them recognized it in accordance with the IFRS norms or CVM determinations. It can be concluded that the degree of adherence of companies to the IFRS norms in the recognition of convertible bonds was very low. Despite the fact IFRS set accounting rules for the classification and measurement of compound financial instruments, and despite CVM’s incisive action towards the observation of such rules, the analysis carried out in this work revealed that most of the companies, five out of six, completely ignored the rules in their accounting practices, choosing only to recognize the issuance of equity or liability instruments without complying with measurement and recognition requirements